Antibodies to neuronal targets in neurological and psychiatric diseases. - Vincent, A; Dalton, P; Clover, L; Palace, J; Lang, B (2003)
The role of antibodies to specific neuronal and muscle ion channels in the etiology of neuromuscular transmission disorders is now well accepted. In addition, maternal antibodies can cross the placenta and cause neonatal disease or even alter the development of the infant, raising the possibility that some neurodevelopmental conditions could be caused by maternal antibodies. Voltage-gated ion channels are expressed in the brain as well as at the neuromuscular junction, and in recent years it has become clear that antibodies to some central nervous system (CNS) channels can be associated with CNS disease. This review highlights features of these conditions, preliminary investigations into neurodevelopmental disorders, and areas for further study.